Distribution and growth potential of wild Pittosporum tobira in the subtropical supratidal zone - Xiaojiao Pan; Pengcheng Wang; Mingjun Teng; Manzhu Bao (Global Ecology and Conservation, 2024)
The use of local native plant species for ecological restoration and rehabilitation is considered an important strategy for nature-based solutions. To achieve this goal, the key work is to understand the distribution of local native plants and their limiting factors. Pittosporum tobira is a keystone species of the vegetation community in subtropical coastal areas, and it plays an essential role in the function and stability of the coastal vegetation buffer zone. The aim of this study was to identify the factors that restrict the growth of P. tobira in the subtropical supratidal zone. We investigated the growth and development of P. tobira plants at three field sites, Dongtou Island (DT), Yuhuan Island (YH), and Cangnan County (CN), in Zhejiang Province, China. To investigate the key factors restricting the growth of this species, we sampled soils from both the supratidal zone and the P. tobira habitat zone. Soils in the supratidal zone showed typical characteristics of sodium chloride-type saline-alkali soil, and the soluble salts content showed wide fluctuations. Some soils in the supratidal zone showed severe salinization. The soil pH and soluble salts contents were higher, but soil organic matter content was lower, in the supratidal zone than in the P. tobira habitat zone. Among the three wild P. tobira habitat sites, DT had the lowest soil nutrient contents. In soil from the DT site, the soluble salts content was 150 % higher and soil organic matter content was 50 % lower than those in soils from the YH and CN sites. Compared with P. tobira growing at the CN and YH sites, those growing at the DT site showed higher antioxidant enzyme activity, higher organic osmotic regulatory substances content, and lower malondialdehyde content in the leaves and roots. These results suggest that the growth and distribution of P. tobira are affected by the organic matter content, pH, and soluble salts content in soil. Among the three P. tobira populations studied here, the population at DT was the most tolerant to the highly saline conditions in this subtropical coastal area, and has potential applications in landscape restoration of the supratidal zone.